Inhibition of lymphocyte proliferation stimulated by lectins and allogeneic cells by normal plasma lipoproteins (The Rockefeller University Press, 1977)
Lipoproteins, isolated by sequential flotation at densities 1.006, 1.019, 1.063, and 1.21, were examined for their ability to inhibit human lymphocytes stimulated by allogeneic cells and by lectins (phytohemagglutinin-P and concanavalin A). All the classes of normal plasma lipoproteins inhibited lymphoproliferation when peripheral blood lymphocytes were cultured in autologous, heterologous, or lipoprotein- deficient plasma (d greater than 1.21). The rank order of inhibitory potency was intermediate density lipoprotein (IDL) greater than very low density lipoproteins (VLDL) greater than low density lipoproteins (LDL) greater than high density lipoproteins (HDL), regardless of the mode of stimulation. The concentrations of IDL, VLDL, and LDL required for complete inhibition of stimulated lymphoproliferation were considerably below the levels of each of these lipoproteins normally found in human plasma. In addition, the concentration of HDL required for 50-90% inhibition was in the range of HDL levels normally found in human plasma. Moreover, at relatively higher concentrations, lipoproteins suppressed the incorporation of [3H]thymidine into DNA below the levels seen with reseting, unstimulated lymphocytes. The results suggest that circulating lymphocytes may normally be highly suppressed by the combined effects of all the endogenous lipoproteins and that the lipoproteins may play important roles in vivo in modulating lymphocyte functions and responses.